A relaxometric method for the assessment of intestinal permeability based on the oral administration of gadolinium‐based MRI contrast agents. (11th February 2016) - Gianolio, Eliana; Boffa, Cinzia; Orecchia, Valeria; Bardini, Paola; Catanzaro, Valeria; Poli, Valeria; Aime, Silvio
Abstract : Herein, a new relaxometric method for the assessment of intestinal permeability based on the oral administration of clinically approved gadolinium (Gd)‐based MRI contrast agents (CAs) is proposed. The fast, easily performed and cheap measurement of the longitudinal water proton relaxation rate ( R 1 ) in urine reports the amount of paramagnetic probe that has escaped the gastrointestinal tract. The proposed method appears to be a compelling alternative to the available methods for the assessment of intestinal permeability. The method was tested on the murine model of dextran sulfate sodium (DSS)‐induced colitis in comparison with healthy mice. Three CAs were tested, namely ProHance®, MultiHance® and Magnevist®. Urine was collected for 24 h after the oral ingestion of the Gd‐containing CA at day 3–4 (severe damage stage) and day 8–9 (recovery stage) after treatment with DSS. The Gd content in urine measured by 1 H relaxometry was confirmed by inductively coupled plasma‐mass spectrometry (ICP‐MS). The extent of urinary excretion was given as a percentage of excreted Gd over the total ingested dose. The method was validated by comparing the results obtained with the established methodology based on the lactulose/mannitol and sucralose tests. For ProHance and Magnevist, the excreted amounts in the severe stage of damage were 2.5–3 times higher than in control mice. At the recovery stage, no significant differences were observed with respect to healthy mice. Overall, a very good correlation with the lactulose/mannitol and sucralose results was obtained. In the case of MultiHance, the percentage of excreted Gd complex was not significantly different from that of control mice in either the severe or recovery stages. The difference from ProHance and Magnevist was explained on the basis of the (known) partial biliary excretion of MultiHance in mice. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new relaxometric method for the assessment of intestinal permeability based on the oral administration of clinically approved gadolinium (Gd) contrast agents is proposed. The fast, easy and relatively cheap measurement of the longitudinal relaxation rate in urine reflects the excretion rate of the paramagnetic probe, and is a compelling alternative to the available clinical methods for the measurement of the intestinal permeability. ProHance ® and Magnevist ® appear to be good probes to assess changes in intestinal permeability.